ANALYSIS OF THE ASPECT CONTEXT OF THEBIOLOGYTEXTBOOK CURRICULUM 2013AT THE CONCEPT OF ENVIRONMENT POLLUTION ON 10th GRADE - Devi Afrilia Varisca; Mila Ermila Hendriyani; Ika Rifqiawati (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2019)
Research was conducted to obtain information about the scope of aspects of context in the curriculum biology 2013 used by students class X serang city in the chapter on environmental pollution and waste recycling.Aspects of context that consist of the scope of context (personal, local and global) and discussion of the field of science regarding health and disease, natural resources, environmental quality, hazards and limits of science and technology. This research is a descriptive study that uses document analysis methods to describe the emergence of context aspects in the material component of the environmental assessment chapter contained in the analyzed textbook. Assessment of analysis uses instruments that have been adjusted to the content of scientific literacy in the PISA 2015 draft. Analysis of the research data uses descriptive statistics by calculating the number of analysis components that are in accordance with indicators of aspects of the context. The results of the analysis show, the two textbooks have applied content aspects of context with an unbalanced percentage. The scope of the dominating context is global space of 71.6%, and context of the discussion about hazards is 41.7%. Whereas the aspect of  context that is very few emerges is in the local / national context space of 4.6% and in the context of the field of discussion in the field of science which has a slight appearance of natural resources of 4.7%.Keywords : aspects of context, biology textbook curriculum 2013, environmental pollution